2003
DOI: 10.1046/j.1360-0443.2003.00335.x
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine versus methadone maintenance therapy: a randomized double‐blind trial with 405 opioid‐dependent patients

Abstract: Buprenorphine did not differ from methadone in its ability to suppress heroin use, but retained approximately 10% fewer patients. This poorer retention was due possibly to too-slow induction onto buprenorphine. For the majority of patients, buprenorphine can be administered on alternate days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
180
0
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(195 citation statements)
references
References 27 publications
11
180
0
4
Order By: Relevance
“…A recent large double-blind randomized controlled trial found that only 52% of methadone subjects were retained after 13 weeks (Mattick et al, 2003). Metaanalyses of psychotherapy studies that exclude those purely with substance abuse have found average dropout rates of about 50% across the treatment outcome literature (Wierzbicki & Pekarik, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…A recent large double-blind randomized controlled trial found that only 52% of methadone subjects were retained after 13 weeks (Mattick et al, 2003). Metaanalyses of psychotherapy studies that exclude those purely with substance abuse have found average dropout rates of about 50% across the treatment outcome literature (Wierzbicki & Pekarik, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the effi cacy of buprenorphine and methadone give inconsistent results, depending on various factors, such as dose height and application fl exibility [15,16,21] Also, the age, sex, length of heroin using, the severity of the symptoms of dependence, have an impact on the eff ectiveness of treatment by one or the other drug, so there are diff erent recommendations for the "fi rst line" in the treatment. Th e higher market price of buprenorphine restricts its widespread use compared to methadone.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by a slow increase in maximal blood concentrations (4 hours), long half-life (25 hours), which supports its therapeutic efficacy, but also the cumulative eff ect aft er repeated dose and increased tolerance, indicating its addictive potential. Numerous of clinical studies [15,16] have shown its eff ectiveness, both on the underlying clinical symptoms of addiction, and on social and health implications, such as reducing the risk for HIV, reducing the addiction-related crime. Th e eff ectiveness of methadone therapy in terms of treatment retention and recidivism varies from study to study [16], from 20% to 70%, with a number of factors being aff ected as a genetic variability, specifi c metabolic characteristics, other medication, the use of other psychoactive substances, etc.…”
Section: Discussionmentioning
confidence: 99%
“…La buprénorphine à haut dosage est apparue sur le marché vers le milieu des années 1990 et constitue une autre approche pharmacologique dont l'efficacité est comparable à celle de la méthadone (Kakko & al., 2007 ;Giacomuzzi & al., 2003 ;Mattick & al., 2003 ;Schottenfeld & al., 2005). La réten-tion est cependant légèrement supérieure avec la méthadone.…”
Section: Palabras Clave: Metadona Buprenorfina Dependencia a Los Opunclassified